An Optimal Medium Supplementation Regimen for Initiation of Hepatocyte Differentiation in Human Induced Pluripotent Stem Cells. Issue 8 (August 2015) - Tomizawa, Minoru; Shinozaki, Fuminobu; Motoyoshi, Yasufumi; Sugiyama, Takao; Yamamoto, Shigenori; Ishige, Naoki
ABSTRACT Human induced pluripotent stem (hiPS) cells are an ideal source for hepatocytes. Glucose and arginine are necessary for cells to survive. Hepatocytes have galactokinase (GALK), which metabolizes galactose for gluconeogenesis, and ornithine transcarbamylase (OTC), which converts ornithine to arginine in the urea cycle. Hepatocyte selection medium (HSM) lacks both glucose and arginine, but contains galactose and ornithine. Although human primary hepatocytes survive in HSM, all the hiPS cells die in 3 days. The aim of this study was to modify HSM so as to initiate hepatocyte differentiation in hiPS cells within 2 days. Hepatocyte differentiation initiating medium (HDI) was prepared by adding oncostatin M (10 ng/ml), hepatocyte functional proliferation inducer (10 nM), 2, 2'‐methylenebis (1, 3‐cyclohexanedione) (M50054) (100 μg/ml), 1× non‐essential amino acid, 1× sodium pyruvate, nicotinamide (1.2 mg/ml), L‐proline (30 ng/ml), and L‐glutamine (0.3 mg/ml) to HSM. HiPS cells (201B7 cells) were cultured in HDI for 2 days. RNA was isolated, used as template for cDNA, and subjected to real‐time quantitative polymerase chain reaction. Alpha‐fetoprotein, γ‐glutamyl transpeptidase, and delta‐like 1 were upregulated. Expression of albumin was not observed. Expression of transcription factors specific to hepatocytes was upregulated. The expression of GALK2, OTC, and CYP3A4 were increased. In conclusion, differentiation of 201B7 cells to hepatoblast‐like cells was initiated in HDI. Limitations were small number of cells were obtained, and the cells with HDI were not mature hepatocytes. J. Cell. Biochem. 116: 1479–1489, 2015. © 2015 Wiley Periodicals, Inc.